(untitled) (Journal of Human Sciences, 2019)
This paper discusses one of the reasons leading to the end of the job relationship between the employee and his/her work. This is done by the will of the administration, as it is responsible for running public facilities regularly and steadily at all times. Whatever the circumstances surrounding this or that facility, the legislator has given it complete freedom to choose who performs this task from the date s/he took the job until the employee reaches the age of retirement. Thus, the administration has the right to keep some employees and dispense the others, whenever it sees that this work serves public interests. What it should be noted is that the authority owned by the administrative is not absolute authority and unrestricted, but is subject to the supervision of the administrative judiciary when the administration depart from the principle of legality. This process makes its decision could be cancelled as a result of one of the pillars of the administrative decision. Thus, we can argue that the administration possesses the dismissal of the employee whenever it deems that it serves the public interest, but we nevertheless confirm that this authority, even if it is discretionary in terms of its use, remains subject to judicial control in terms of the legality of the dismissal decision, and the extent of its conformity with the law in its broad sense.